Ermüdung im Fußballspiel - Erklärungsversuche und Konsequenzen - Portela, J.; Hartmann, U. (Leipziger Sportwissenschaftliche Beiträge, 2016)
The article addresses point of views of fatigue mechanisms during a football game. Concerning currently aspects under discussion, it tries to explain these from a physiological point of view and to discuss possible consequences of training methodology.